2017
DOI: 10.1016/j.celrep.2017.09.069
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Gene Bmal1 Controls Thyroid Hormone-Mediated Spectral Identity and Cone Photoreceptor Function

Abstract: SUMMARY Circadian clocks regulate various aspects of photoreceptor physiology, but their contribution to photoreceptor development and function is unclear. Cone photoreceptors are critical for color vision. Here, we define the molecular function of circadian activity within cone photoreceptors and reveal a role for the clock genes Bmal1 and Per2 in regulating cone spectral identity. ChIP analysis revealed that BMAL1 binds to the promoter region of the thyroid hormone-activating enzyme type 2 iodothyronine deio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 56 publications
7
56
1
Order By: Relevance
“…Dio2 2/2 mice have been shown to have impaired photoreceptor function. Sawant et al (61) reported reduced rod and cone ERG responses in Dio2 2/2 mice. Ng et al (29) showed reduced rod ERG response in Dio2 2/2 mice.…”
Section: Dio2 Deficiency Improves Cone Survival and Function In Rpe65mentioning
confidence: 98%
“…Dio2 2/2 mice have been shown to have impaired photoreceptor function. Sawant et al (61) reported reduced rod and cone ERG responses in Dio2 2/2 mice. Ng et al (29) showed reduced rod ERG response in Dio2 2/2 mice.…”
Section: Dio2 Deficiency Improves Cone Survival and Function In Rpe65mentioning
confidence: 98%
“…). RORA binds to ROR‐responsive element ( RORE ) in the promoter region of Bmal1 and positively regulates Bmal1 transcription . We showed that miR‐10a is also a rhythmic gene similar to Bmal1 , and interestingly, rhythmic change of Bmal1 was blunted by the overexpression of miR‐10a (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…The expression of Bmal1 fluctuates in an approximately 24-hour cycle in contrast to the period circadian clock 2 (per2) gene, which fluctuates in an opposite phase. (29) Contrary to humans, in nocturnal mice and rats administered a meal at night, expression levels of Bmal1 were elevated at night but low during the day. (18) In liver-specific Bmal1-KO mice, a considerable reduction of genes associated with lipid neogenesis (SREBP1c, FASN, acetyl-coenzyme A [CoA] carboxylase 1 [ACC1], and stearoyl-CoA desaturase 1 [SCD1]) was observed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…26 It is likely that the tissue-specific effect of thyroid hormones on the regulation of PER2 expression implicates the involvement of additional mechanisms. 27 Tissue-specific circadian expression of thyroid hormone receptors (TR) represents an additional level of regulation besides the HPA. 27 Tissue-specific circadian expression of thyroid hormone receptors (TR) represents an additional level of regulation besides the HPA.…”
Section: Clock Genes and Thyroid Disordersmentioning
confidence: 99%